Design Thinking Approach in the Development of E-Worksheets and AI Videos to Enhance Problem-Solving Skills of Senior High School Students - Agustina, Mela; Purwosetiyono, F.X. Didik; Buchori, Achmad; Osman, Sharifah (Department of Mathematics Education Program IPI Garut, 2026)
Penelitian ini bertujuan mengembangkan rancangan e‑worksheet dan video AI melalui pendekatan design thinking untuk meningkatkan pemecahan masalah siswa SMA di Kota Pekalongan. Subjek penelitian terdiri atas 143 siswa dan 14 guru dari beberapa SMA berbeda yang terlibat pada tahap empathize dan define untuk mengidentifikasi profil permasalahan pembelajaran, yang menunjukkan bahwa pemecahan masalah kurang berkembang karena pembelajaran masih abstrak, berfokus pada hafalan, serta minim media interaktif sementara guru terkendala waktu bimbingan. Pada tahap ideate, melalui telaah literatur dan meta‑analisis, dikembangkan gagasan E‑TopWorksheets dengan Pendekatan Matematika Realistik berbantuan Mootion AI; hasil meta‑analisis menunjukkan nilai p<0,001 dengan effect size 0,841 yang menandakan pengaruh signifikan dan kuat penggunaan media serupa terhadap peningkatan pemecahan masalah matematika yang berpotensi menjadi dasar pengembangan media dan memerlukan pengujian lanjutan. Disimpulkan bahwa pendekatan design thinking efektif sebagai kerangka kerja pengembangan prototype media yang kontekstual, adaptif, dan berkontribusi pada inovasi media pembelajaran yang relevan dengan tuntutan pembelajaran abad ke‑21. This study aims to develop a design for e-worksheets and AI-based videos using a Design Thinking approach to enhance the problem-solving skills of Senior High School (SMA) students in Pekalongan City. The research subjects consisted of 143 students and 14 teachers from various high schools who were involved in the empathize and define stages to identify learning problem profiles; findings indicated that problem-solving skills were underdeveloped due to abstract instruction focused on rote learning, a lack of interactive media, and teachers' constraints regarding guidance time. In the ideate stage, through literature review and meta-analysis, the concept of E-TopWorksheets using a Realistic Mathematics Education approach assisted by Mootion AI was developed. The meta-analysis results showed a p-value < 0.001 with an effect size of 0.841, indicating a significant and strong influence of similar media on improving mathematical problem-solving, which potentially serves as a basis for media development and requires further testing. It is concluded that the Design Thinking approach is effective as a framework for developing contextual and adaptive media prototypes, contributing to learning media innovation relevant to 21st-century learning demands.